Gold Sterile Ore Acid Generation Evaluation, San Juan Argentina - Bazan Brizuela, Vanesa Lucia (2014)
One of the problems that mining represents in relation to the natural watercourses is the possible formation of what we call acid mine drainage, which consists in the emission or formation of water effluents of great acidity, usually rich in sulfate and with variable contents in heavy metals. The drainage mentioned is developed from the metal sulfide and sulfate leaching. Researches about the creation of acid drainage suggest that the formation of these depends directly on various factors: primary mineralogy (neutralizer sulfides and minerals), water presence (whether), oxygen diffusion, grain size, microbiological interaction (bacterium), among others. To study these variables and to relate them with geological factors, static (Acid-Base Accounting) and dynamic (Humidity Cell) tests have been developed, among others. The mentioned tests are applied to a case of a gold deposit situated in the Province of San Juan, which is currently very argued because of its mining activity due to its leaching process. In the sterile mineral obtained from the process, kinetics tests were carried out in humidity cells to simulate the natural oxidation of the primary mineral samples. In the obtained leaching, pH values closer to neutrality and a limited solution metal presence were detected, indicating the neutralization ability due to the carbonates ores presence.